Loss of heterozygosity on chromosomes 10q, 9p, 17p and 13q in malays with malignant glioma. - Zainuddin, Norafiza; Jaafar, Hasnan; Isa, Mohd. Nizam; Abdullah, Jafri Malin (Maney Publishing, 2004)
Recent advances in neuro-oncology have revealed different pathways of molecular oncogenesis in malignant gliomas including loss of heterozygosity on chromosomal regions harboring tumor suppressor genes. In the present study, we performed polymerase chain reaction-loss of heterozygosity (PCR-LOH) analysis using microsatellite markers to identify loss of heterozygosity on chromosomes 10q, 9p, 17p and 13q in the Malays with malignant gliomas. Of 12 cases with allelic losses, seven (58.3%) cases showed LOH on chromosome 10q, three (25.0%) cases showed LOH on chromosome 9p, four (33.3%) cases showed LOH on chromosome 17p and two (16.7%) cases showed LOH on chromosome 13q. The cases include five (41.7%) cases of glioblastoma multiforme, three (25.0%) cases of anaplastic astrocytoma, three (25.0%) cases of anaplastic oligodendroglioma and one (8.3%) case of anaplastic ependymoma. Four cases showed loss of heterozygosity on more than one locus. Our findings showed that loss of heterozygosity on specific chromosomal regions contributes to the molecular pathway of glioma progression in Malay population. In addition, these data provide useful evidence of molecular genetic alterations of malignant glioma in South East Asian patients, particularly in the East Coast of Malaysia.